2022
DOI: 10.1039/d2lc00197g
|View full text |Cite
|
Sign up to set email alerts
|

Tuning particle inertial separation in sinusoidal channels by embedding periodic obstacle microstructures

Abstract: Inertial microfluidics functions solely based on fluid dynamics at relatively high flow speed. Thus, channel geometry is the critical design parameter that contributes to the performance of the device. Four...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 75 publications
(120 reference statements)
2
15
0
Order By: Relevance
“…Lu et al and Cha et al first reported periodic contraction structures to improve inertial sorting. 51,53 We have modified this approach to isolate small-diameter cancer cells (A549 lung cancer cells) from blood samples and breast cancer cells from blood plasma. We report an improvement in cell recovery and separation enrichment when compared to extant approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al and Cha et al first reported periodic contraction structures to improve inertial sorting. 51,53 We have modified this approach to isolate small-diameter cancer cells (A549 lung cancer cells) from blood samples and breast cancer cells from blood plasma. We report an improvement in cell recovery and separation enrichment when compared to extant approaches.…”
Section: Introductionmentioning
confidence: 99%
“…The fully automated and portable platform can harvest up to 0.4 million of intact WBCs from 50 μL of human peripheral blood. More complex channel geometries beyond the classical straight or spiral layout may lead to improved inertial-based separation techniques . Embedding periodic concave and convex obstacle microstructures in sinusoidal channels can significantly enhance the Dean flow and tune the flow range for particle inertial focusing and separation.…”
Section: Instrumentationmentioning
confidence: 99%
“…[4] For instance, curved microchannels take advantage of inertial force to create a pressure gradient normal to the main flow, triggering Dean flow to enhance the convection effect. [14][15][16] Various curved microchannels, including serpentine channel, [17][18][19] helical channel, [20][21][22] and twisted channel, [23] were usually designed into passive micromixers. Besides, through integrating different microstructures, including herringbone structure, [24][25][26] Tesla structure, [4,27] barriers on the channel, [9,28,29] and cross-linked channel in microchannels, [30,31] the fluid inside could be folded, split, stretched, enlarged or recombined to increase the interfacial contact area and then induce chaotic advection.…”
Section: Introductionmentioning
confidence: 99%